Ground motion simulation for dynamic structural analysis: pros and cons - Estêvão, João M. C. (2012)
In many seismic codes the use of simulated ground motions for dynamic structural analysis is already considered. However, from the structural engineer point of view, the use of such simulated accelerograms is not very attractive, mainly because more seismological knowledge background is needed. For this reason, a user friendly freeware computer program named SIMULSIS was developed to help structural engineers to generate simulated accelerograms. A new finite-fault stochastic method was developed for ground motion simulation and implemented in the program together with an equivalent linear model that accounts for superficial soil dynamic amplification. The capabilities of the program and the precision of results produced are illustrated by the simulations carried out for two recorded earthquakes. Moreover, some suggestions related to the use of the developed computer program not only for seismic structural analysis purposes but also in the future generation of hazard maps are presented.